Legal Protection of Geographical Indication of Salak Sidimpuan in South Tapanuli District North Sumatera - Arieza, Cahya Putri (Jurist-Diction, 2025)
This research aims to know and understand the permission to use Geographical Indications of Salak Sidimpuan for salak farmers when registering with the South Tapanuli Regional Government and the legal remedies taken if salak farmers in other regions want to register Geographical Indications of Salak Sidimpuan. The type of research used is normative legal research. The efforts made by the South Tapanuli Regency government are only limited to maintaining the reputation of Salak Sidimpuan as protection for cooperatives in the field of salak fruit processing. Even though Salak Sidempuan qualifies as a Geographical Indication product as stated in article 6 of PP No. 51 of 2007. In the form of preventive protection, Salak Sidimpuan must first be registered with the DJKI in order to obtain legal protection. Repressive forms of protection are carried out by non-litigation channels that can be carried out through arbitration or alternative dispute resolution.